The Impact of Various Physiotherapy Programs on the Balance, Knee Proprioception, and Flexors/Extensors Strength after Anteriorcruciate Ligament Reconstruction - Vilma Juodžbalienė; Akvilė Šimkuvienė; Marius Brazaitis; Tomas Darbutas (Lithuanian Sports University, 2020)
The decrease in knee flexors and extensors strength and poor balance are related to the impairment of the knee proprioception after anterior cruciate ligament reconstruction [1, 2]. Therefore, it is important to assess the impact of various physiotherapy programs on static balance, knee proprioception, and thigh muscle strength, and at the same time pursue the qualitative rehabilitation as well as look for the possibilities of assessment of knee proprioception using the isokinetic dynamometer. Twenty volunteers (aged 26-36 years) participated in the study four-five weeks after anterior cruciate ligament reconstruction. The participants were divided into two groups: trial group (n = 10; two women, eight men) and control group (n = 10; two women, eight men). Complementary neuromuscular training and the ordinary physiotherapy program were applied to the trial group for three weeks; the control group received only the ordinary physiotherapy program. Static balance (using Balance error scoring system), knee proprioception (using the isokinetic dynamometer), and thigh muscle strength (using Lovett scale) were determined before and after the three-week intervention period. Participants had to indicate the position of the tested leg, i. e. whether the knee was flexed at 30 or 60 degrees. We established the difference between the indicated and real position of the leg in degrees. The mentioned difference indicated the state of knee proprioception. The outcomes of static balance significantly improved after three weeks of physiotherapy in both groups: trial group - from 12.3 ± 3.4 to 2.1 ± 0.8 errors (p < 0.01), control group - from 12.2 ± 1.6 to 4.2 ± 0.9 errors (p < 0.01). Also, the trial and control groups demonstrated improved condition of knee proprioception at both angular velocities of 15 degrees/s and 30 degrees/s. There were no differences between standard means of knee flexors strength before the intervention. The outcomes of knee flexors strength of the trial group were significantly higher as compared to the outcomes demonstrated by the control group (p < 0.05). There were no significant differences in knee extensors strength between both groups. Thus, values of static balance, knee proprioception, and flexors/extensors strength change more rapidly when frequent and longer neuromuscular training is applied. The ordinary physiotherapy program has a positive but less effect on the above mentioned variables. Keywords: anterior cruciate ligament, static balance, proprioception, muscle strength, neuromuscular training.